Ritual cepa lingko dan tahun Sabat: Sebuah pemahaman keadilan berladang orang Manggarai - Benediktus Denar; Antonius Denny Firmanto (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2022)
This article aims to introduce justice in the provisions of the Sabbath year held in the Christian Scripture and its encounter with the cepa lingko ritual in the farming tradition of the Manggarai people, East Nusa Tenggara (NTT). Ethnography is used to collect data for this research, while the data are analyzed and presented using a qualitative approach. This research concludes that the basis of the Sabbath provisions is the creator's will that upholds ecological justice and social justice. The values contained in the requirements of the Sabbath are also essential aspects contained in the cepa lingko ritual, which materializes in the farming tradition of the Manggarai people, NTT. So, there is an authentic encounter between the values of the biblical Sabbath and the traditional Manggarai sabbath, especially in the provisions of the cepa lingko ritual. These values can be essential themes in the inculturation of environmental theology and the theology of social justice, especially among the Manggaraian community, who are predominantly Catholic and still adhere to their ancestors??